LOW TEMPERATURES EFFECT ON THERMAL CONDITIONS OF DZ-98 AUTOGRADER HYDRAULIC UNITS - T. N. Okhlopkov (Вестник СибАДИ, 2020)
Introduction. The article discusses the climatic conditions of Yakutia, as well as the cooling process of the hydraulic system of DZ-98 motor grader in order to prevent violation of the thermal regime of hydraulic units under the influence of low temperatures, taking into account the wind blowing and operating conditions. The surface temperature of the hydraulic units was measured on January 16, 2018 in the city of Yakutsk on the basis of Yakutdorstroi joint-stock company at an ambient temperature of -42 ° С.Materials and methods. To ensure a reliable operation of the hydraulic system at low temperatures, hydraulic units must provide a supply of working fluid under pressure, regardless of changes in ambient temperature. The thermal regime of hydraulic units is characterized by three main parameters: pressure, temperature and volume. In the North, where the ambient winter temperature varies from -27 ° С to -49 ° С, the absolute temperature is the determining parameter. Studying the problem, theories of heat conduction and heat transfer in solids, hydrodynamics, and differential equations were used.Results. Natural and climatic data, as well as the recorded surface temperature of hydraulic units, allow to determine the number of days with a critically negative temperature, the heat transfer of hydraulic units and the regularity of its change depending on the operating mode.